Concurrent sequence analysis of 5' and 3' RNA termini by intramolecular circularization reveals 5' nontemplated bases and 3' terminal heterogeneity for lymphocytic choriomeningitis virus mRNAs. - Meyer, B J (1993)
We have used a technique of RNA circularization coupled with polymerase chain reaction amplification for simultaneous analysis of the 5' and 3' termini of subgenomic mRNAs derived from the S RNA of lymphocytic choriomeningitis virus during an acute infection of BHK cells. These mRNAs possess 1 to 7 nontemplated nucleotides of apparently random sequence at their 5' ends. The predominant mRNA species have 4 or 5 nontemplated nucleotides. The 5' termini of the mRNAs also have properties consistent with the presence of a 5' cap structure. The 3' termini of the mRNAs lack poly(A) tails, and we have shown that transcription termination occurs at heterogeneous positions within the intergenic region of the S RNA. The identification of several distinct termini in the vicinity of a putative stem-loop structure in the RNA templates suggests that transcription termination may be mediated by a structural signal rather than a precise sequence signal.